2013
DOI: 10.1073/pnas.1218515110
|View full text |Cite|
|
Sign up to set email alerts
|

mChIP-KAT-MS, a method to map protein interactions and acetylation sites for lysine acetyltransferases

Abstract: Significance Recent proteomic studies have revealed that lysine acetylation is a global and ubiquitous posttranslational modification. However, in the vast majority of cases the lysine acetyltransferases (KATs) responsible for individual modifications remain unknown. Here we present a unique methodology that connects KATs to their substrates. To validate the methodology, we use the yeast KAT nucleosome acetyltransferase of histone H4 (NuA4) and identify both protein interactions and acetylation targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 64 publications
(95 reference statements)
0
40
0
1
Order By: Relevance
“…However, enhanced histone acetylation could not rescue all esa1D sds3D phenotypes, suggesting that balanced acetylation of both histone and nonhistone substrates of Esa1 is critical for robust growth in the absence of this essential enzyme. Supporting this idea, in proteomic studies .200 nonhistone substrates have been reported for NuA4 (Lin et al 2009;Mitchell et al 2013), and of these, at least 77 are encoded by essential genes. Substrates include components of the chromatin-remodeling complex RSC (e.g., STH1 and RSC8), proteins involved in ribosome biogenesis (e.g., NOP4 and DBP6), and cytoskeleton and spindle components (e.g., TUB2 and SPC42), whose acetylation state and role in viability in esa1D and esa1D sds3D remain to be tested.…”
Section: Discussionmentioning
confidence: 91%
“…However, enhanced histone acetylation could not rescue all esa1D sds3D phenotypes, suggesting that balanced acetylation of both histone and nonhistone substrates of Esa1 is critical for robust growth in the absence of this essential enzyme. Supporting this idea, in proteomic studies .200 nonhistone substrates have been reported for NuA4 (Lin et al 2009;Mitchell et al 2013), and of these, at least 77 are encoded by essential genes. Substrates include components of the chromatin-remodeling complex RSC (e.g., STH1 and RSC8), proteins involved in ribosome biogenesis (e.g., NOP4 and DBP6), and cytoskeleton and spindle components (e.g., TUB2 and SPC42), whose acetylation state and role in viability in esa1D and esa1D sds3D remain to be tested.…”
Section: Discussionmentioning
confidence: 91%
“…Future investigations might benefit from recently developed techniques, such as targeted NGS in large-scale screening and the combination of ChIP and mass spectrometry, to determine the interactome of histone modification writers and readers [96]. Highly sensitive quantitative mass spectrometry may be used as a sensitive and alternative measure, if the dynamics of histone changes must be focused and the amount of available ChIP DNA is limited [97].…”
Section: Discussionmentioning
confidence: 99%
“…Although we identified acetylation sites on 27 of these proteins in experiments employing the esa1-ts mutation, none of these sites were defined as Esa1-regulated using our stringent criteria (supplemental Tables S1 and S2). A separate study by Mitchell et al (13), identified 38 proteins acetylated by the Esa1-containing complex NuA4 in vitro. Our analysis identified four of these proteins (Esa1, Eaf3 Epl1, and Yng2 -all members of the NuA4 complex) as having high or medium confidence Esa1-regulated sites.…”
Section: Fig 7 Ada2 Selectively Regulates Gcn5-dependent Acetylationsmentioning
confidence: 99%
“…Although recent efforts have demonstrated that acetylation is a frequent post-translational modification, little is known about the regulation of most of these marks (12)(13)(14)(15). Moreover, although recruitment to chromatin is seen as the key step in acetylation of histone tails, little is known about the mechanism behind non-histone substrate selection.…”
mentioning
confidence: 99%